Investigation of regularity of plasma formation in large volume on the basis of the hollow cathode effect using high-frequency short-pulsed voltage; The 7th International Forum on Strategic Technology (IFOST-2012), September 18-21, 2012, Tomsk - Ryabchikov A. I. Aleksandr Ilyich; Sivin D. O. Denis Olegovich; Ananin P. S. Petr Semenovich; Додорин К. Ю. Константин Юрьевич (2012, 2012)
Title screen